Use of elderberry polyphenol compounds in the manufacture of juicy beverages - Tokarenko, S.A.; Romanov, O.S.; Romanova, Zoriana; Kosoholova, Liudmyla (Problems of Environmental Biotechnology, 2021)
The nutritional value of wild plant raw materials is determined by the content of nutrients: vitamins, minerals and other important components that play an important role in human nutrition, regulate metabolic processes, and affect the functions of individual organs. It is important to preserve them for the production of functional drinks.